Self-forgiveness and forgiveness-seeking in response to rumination: Cardiac and emotional responses of transgressors. Issue 4 (4th July 2017) - da Silva, Sérgio P.; vanOyen Witvliet, Charlotte; Riek, Blake
Abstract: Self-forgiveness and forgiveness-seeking are important and understudied aspects of forgiveness. We examined the cardiac and emotional patterns of healthy young adults (40 women, 40 men) who recalled an unresolved offense they had caused another person. Participants engaged in four imagery conditions: ruminating about the offense, being humbly repentant and engaging in self-forgiveness, seeking forgiveness from the victim and receiving forgiveness, and seeking forgiveness from the victim and being begrudged. Being repentant and begrudged forgiveness by one's victim was associated with the same level of guilt as when ruminating, but significantly more negative emotion, less control, and less empathy than when ruminating, self-forgiving, and receiving forgiveness from the victim. Compared to ruminating about one's wrongdoing, self-forgiving alleviated guilt and negative emotion, increased perceived control, decreased heart rate, and increased parasympathetic activation. Imagery of receiving forgiveness from the victim resulted in these same patterns and was equivalent to self-forgiveness across variables.